Postmodern feminist pedagogy in history education at a public senior high school in Palembang - Dhita, Aulia Novemy; Supriatna, Nana; Saripudin, Didin; Wiyanarti, Erlina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
History education has traditionally been dominated by masculine narratives and has paid limited attention to contemporary social issues. In response to this imbalance, this study aims to explore the implementation of a postmodern feminist approach in the teaching of history. The research employed a case study method with purposive sampling, selecting a Grade 10 history teacher at SMA Negeri 20 Palembang, due to her direct involvement in applying postmodern feminist pedagogy. Data were collected through participant observation, semi-structured interviews, and analysis of instructional documents, while data analysis was conducted using pattern matching and explanation-building techniques. The findings indicate that the postmodern feminist approach, applied by the history teacher through the topic of the Majapahit Kingdom, successfully challenges the androcentric orientation of historical content. The learning process is also directed toward contemporary social issues, particularly the subordination of women's roles as mothers. Through a pop-up book project, students depicted not only male figures from the Majapahit Kingdom but also the female ruler Tribhuwanattunggadewi. The postmodern feminist approach opens space for the pluralisation of women’s experiences in historical narratives and fosters a more horizontal and egalitarian relationship between teacher and students.